PENANGANAN KELUHAN MASYARAKAT PADA PELAYANAN KESEHATAN DI PUSKESMAS KECAMATAN PASAN KABUPATEN MINAHASA TENGGARA - TUMUBER, VIVIAN; ROMPAS, WELSON; POMBENGI, JERICHO (Sam Ratulangi University, 2018)
Abstract : This research is based on the handling of public complaints that can not be handled properly by thepuskesmas. The public service system is still constrained, resulting in a demanding society for thedissatisfaction of the services provided. The unavailability of places or containers in receiving variouscomplaints from the community directly, even the unavailability of suggestion boxes or input from thecommunity on services provided by the puskesmas. This research intends to know the Handling of PublicComplaints on Health Service at Puskesmas Pasan District of Southeastern Minahasa. The theory used is thetheory of complaints handling according to Dyah Hariani is the problem of delay in service process, lessfriendly officers, and information that is not clear. The method used is qualitative method with descriptiveapproach. With his instrument as a researcher himself with informants seven people. Data analyst techniquessuch as observation, interview, and documentation. Research location at Puskesmas Kecamatan Pasanlocated in Towuntu Timur village. The result of the research shows that the problem that raises thecomplaints in the community about the health services provided by the puskesmas has not been in accordancewith the expectations of the community. This can be seen from the fact that the problems or complaintssubmitted by the community are handled or responded quickly by the puskesmas. Researchers provide adviceon this research that the importance of paying attention and manage complaints from the public to improvethe quality of public services better. So every government administration needs to pay attention to complaintsfrom the community especially on health services by puskesmas.Keywords: Handling Complaints, Society, Health Services